Comprehensive organic synthesis : selectivity, strategy, and efficiency in modern organic chemistry - Trost, Barry M.; Fleming, Ian, 1935- (Pergamon Press, 1991)
The development of more effective routes to known materials and the production of new materials are important goals in many areas, including electronics, agriculture, medicine and textiles. Organic synthesis is central to achieving these goals. Comprehensive Organic Synthesisdraws together the common themes that underlie the many apparently disparate areas of organic chemistry which underpin synthetic strategies, thus providing a comprehensive overview of this important discipline. The contributions have been organized to reflect the way in which synthetic chemists approach a problem. In terms of organic molecules, the work is divided into formation of carbon-carbon bonds, introduction of heteroatoms and heteroatom interconversions. Thus, Volumes 1-5 focus on carbon-carbon formation, but also include aspects of heteroatom introduction. Volumes 6-8 concentrate on interconversion of heteroatoms, but also deal with exchange of carbon-carbon bonds for carbon-heteroatom bonds. Organization of the chapters is along the theme of selectivity, which is a critical question in determining the suitability of a synthetic method. Volume 9 contains cumulative author and subject indexes. Comprehensive Organic Synthesis will appeal to a wide audience. The set will be an essential reference work for all those seeking information on the solution of synthetic problems, whether they be experienced practitioners or chemists whose major interests lie outside organic synthesis. In addition, synthetic chemists requiring the essential facts in new areas, as well as students completely new to the field, will find Comprehensive Organic Synthesis an invaluable source, providing authoritative accounts of the essential facts and concepts.